MYKOLA HOVORUSHCHENKO (1924–2011): BIOGRAPHY OF A SCIENTIST - Domanovskyi, A.; Домановський, А. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article is devoted to the biography of Mykola Yakovych Hovoruschenko (1924–2011). M. Hovorushchenko is known for his role in the development of the first modern stations of automated diagnostics. Under the direction of M. Hovorushchenko there were trained ap-proximately 8500 engineers, more than 80 patents for inventions were obtained.
МИКОЛА ГОВОРУЩЕНКО (1924–2011): БІОГРАФІЯ НАУКОВЦЯ
НИКОЛАЙ ГОВОРУЩЕНКО (1924–2011): БИОГРАФИЯ УЧЕНОГО
Keywords: Mykola Yakovych Hovoruschenko (1924–2011); biography; scientist; contribution to science; Микола Якович Говорущенко (1924–2011); біографія; науковець; науковий внесок; Николай Яковлевич Говорущенко (1924–2011); биография; ученый; научный вклад; 378.2(092)